The utility of diffusion-weighted magnetic resonance imaging in differentiation of benign and malignant diffuse colon wall thickening - Koç, Mustafa; Serhatlıoğlu, Selami (My University, 2018)
To examine the effectiveness of apparent diffusion coefficient (ADC) values in differentiation of benign bowel wall thickening and malignant diffuse scirrhous type’s bowel wall thickening. Subject and Methods A total of 81 patients who underwent abdomen diffusion-weighted magnetic resonance imaging (DW MRI) in our clinic between April 2015 and September 2016 was analyzed. Of these patients, 42 had benign bowel wall thickening and 39 had malignant bowel wall thickening. The values of ADC were measured with two different b-values (400, 1000 s/mm2). Benign and malignant ADC values were compared using areas under the receiver-operating characteristic (ROC) curve. Results: According to the ADC values, the mean ADC values (x10-3 mm2/s) of benign lesions were 1.42±0.17 for b 400, 1.39±0.12 for b 1000. The mean ADC values (x10-3 mm2/s) of malignant lesions were 1.08±0.15 for b 400, 1.02±0.13 for b 1000. There were significantly lower ADC values in malignant lesions in all b values (P=.001 for b 400, P=.001 for b 1000). ROC analysis showed that a cut-off value of 1.24 x 10-3 mm2/s between the malignant and benign values with a sensitivity of 91 %, specificity of 85 %, and an accuracy of 84 %. The positive predictive value, negative predictive value, and diagnostic accuracy of ADC values were determined to be 97 %, 86 %, and 88 % respectively. Conclusion: Measurement of ADC values by DWI was effective in differentiation of malignant diffuse scirrhous types of bowel wall thickening from benign bowel wall thickening.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji